Bioactivities and Extract Dereplication of Actinomycetales Isolated From Marine Sponges - Santos, José D.; Vitorino, Inês; De la Cruz, Mercedes; Díaz, Caridad; Cautain, Bastien; Annang, Frederick; Pérez-Moreno, Guiomar; Gonzalez Martinez, Ignacio; Tormo, Jose R.; Martín, Jesús M.; Urbatzka, Ralph; Vicente, Francisca M.; et al. (Frontiers in Microbiology, 2019)
In the beginning of the twenty-first century, humanity faces great challenges regarding diseases and health-related quality of life. A drastic rise in bacterial antibiotic resistance, in the number of cancer patients, in the obesity epidemics and in chronic diseases due to life expectation extension are some of these challenges. The discovery of novel therapeutics is fundamental and it may come from underexplored environments, like marine habitats, and microbial origin. Actinobacteria are well-known as treasure chests for the discovery of novel natural compounds. In this study, eighteen Actinomycetales isolated from marine sponges of three Erylus genera collected in Portuguese waters were tested for bioactivities with the main goal of isolating and characterizing the responsible bioactive metabolites. The screening comprehended antimicrobial, anti-fungal, anti-parasitic, anti-cancer and anti-obesity properties. Fermentations of the selected strains were prepared using ten different culturing media. Several bioactivities against the fungus Aspergillus fumigatus, the bacteria Staphylococcus aureus methicillin-resistant (MRSA) and the human liver cancer cell line HepG2 were obtained in small volume cultures. Screening in higher volumes showed consistent anti-fungal activity by strain Dermacoccus sp. #91-17 and Micrococcus luteus Berg02-26. Gordonia sp. Berg02-22.2 showed anti-parasitic (Trypanosoma cruzi) and anti-cancer activity against several cell lines (melanoma A2058, liver HepG2, colon HT29, breast MCF7 and pancreatic MiaPaca). For the anti-obesity assay, Microbacterium foliorum #91-29 and #91-40 induced lipid reduction on the larvae of zebrafish (Danio rerio). Dereplication of the extracts from several bacteria showed the existence of a variety of secondary metabolites, with some undiscovered molecules. This work showed that Actinomycetales are indeed good candidates for drug discovery.